2005
DOI: 10.22358/jafs/66971/2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary conjugated linoleic acid isomers and vitamin E on fatty acid composition and cholesterol content of hen egg yolks

Abstract: The objective of this study was to develop functional eggs, by feeding hens with conjugated linoleic acid (CLA) isomers (0.0 vs 1.5%) and α-tocopherol (0 vs 120 mg/kg of diet) as an antioxidant. Thirtysix 25-week-old laying hens were randomly distributed into four groups of 9 hens and maintained in individual laying cages throughout 12 weeks of experiment. They were assigned to the four commercial layer diets (2770 kcal ME/kg; 16.7% CP): 0.0% CLA, 0.0% CLA+120 mg vit. E/kg of diet, 1.5% CLA and 1.5% CLA + 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In contrast, a decrease in the content of SFAs in egg yolk was reported in hens fed with flaxseed and Rhus coriaria seed or Zingiber officinale root powder as antioxidant sources [60]. Moreover, our results of vitamin E on egg yolk SFAs and MUFAs in this study agreed with the previous report by [61].…”
Section: Fatty Acid Content In Raw Egg Yolkssupporting
confidence: 90%
“…In contrast, a decrease in the content of SFAs in egg yolk was reported in hens fed with flaxseed and Rhus coriaria seed or Zingiber officinale root powder as antioxidant sources [60]. Moreover, our results of vitamin E on egg yolk SFAs and MUFAs in this study agreed with the previous report by [61].…”
Section: Fatty Acid Content In Raw Egg Yolkssupporting
confidence: 90%
“…Hur et al (2003) indicated that lipid oxidation of the egg yolk during cold storage could be inhibited by dietary CLA due not only to the change in fatty acid composition but also to the high concentration of CLA in egg yolk. Szymczyk and Pisulewski (2005) reported that dietary vitamin E increased the rate of laying and egg production per hen and may also exert alleviating effects on fatty acid composition of CLA-enriched eggs.…”
Section: Fatty Acidsmentioning
confidence: 99%